1997
DOI: 10.3109/01485019708988535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroid Status on Pituitary Gonadotropin and Testicular Reserve in Men

Abstract: This investigation was conducted to evaluate the effect of thyroid dysfunction on the pituitary-gonadal axis. Ten men with Graves' disease and 5 hypothyroid patients were studied; 10 normal males were studied as a control group. In untreated conditions hyperthyroidism was associated with a normal serum-free testosterone concentration, an increased serum of 17OHP levels, a reduced testosterone response to hCG stimulation, and a hyperresponse of LH to GnRH. These abnormalities reverted after normalization of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 15 publications
2
29
0
2
Order By: Relevance
“…Most studies indicated that hypothyroid men with hypogonadism have normal LH and FSH levels, suggesting that the primary defect is not in Leydig cells and presumably results from a defect at the hypothalamus and/or pituitary level. Blunted Gn responses to GnRH support this notion, and it would therefore seem that primary hypothyroidism impairs the ability of the pituitary gland to respond to GnRH (41). Another finding that supports the above notion is that hCG produces an exaggerated response of serum testosterone in such patients, which is in contrast with what is expected if the primary defect was in Leydig cells.…”
Section: B Hypothyroidism In Malesmentioning
confidence: 72%
“…Most studies indicated that hypothyroid men with hypogonadism have normal LH and FSH levels, suggesting that the primary defect is not in Leydig cells and presumably results from a defect at the hypothalamus and/or pituitary level. Blunted Gn responses to GnRH support this notion, and it would therefore seem that primary hypothyroidism impairs the ability of the pituitary gland to respond to GnRH (41). Another finding that supports the above notion is that hCG produces an exaggerated response of serum testosterone in such patients, which is in contrast with what is expected if the primary defect was in Leydig cells.…”
Section: B Hypothyroidism In Malesmentioning
confidence: 72%
“…Previous studies indicated that patients with hypothyroidism demonstrated a defective LH response to GnRH [27] and a decrease in the blood level of LH and TSH causing testicular dysfunction [28].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hyperthyroid men have increased 17-hydroxy (17-OH) progesterone, T, and E2 [1,14,30,34,41,47,49,55,101]. The increased level of E2 may be due to increased peripheral metabolism of androgens into estrogen [90].…”
Section: Serum Sex Steroids Under Altered Thyroid Statusmentioning
confidence: 99%